Urban informatics - Shi, Wenzhong ;Goodchild, Michael F. ;Batty, Michael ;Kwan, Mei-Po ;Zhang, Anshu (Singapore : Springer, 2021)
This open access book is the first to systematically introduce the principles of urban informatics and its application to every aspect of the city that involves its functioning, control, management, and future planning. It introduces new models and tools being developed to understand and implement these technologies that enable cities to function more efficiently - to become 'smart' and 'sustainable'. The smart city has quickly emerged as computers have become ever smaller to the point where they can be embedded into the very fabric of the city, as well as being central to new ways in which the population can communicate and act.
Urban Science and Systems -- Urban Sensing -- Urban Big Data Infrastructure -- Urban Computing -- Urban Problems and Possible Solutions -- Perspectives for the Future.
Includes bibliographical references.
Keywords: INFORMATION SOCIETY